Fibrillar collagen genes are not coordinately upregulated with TGF β1 expression in finasteride-treated prostate - Delella, Flávia Karina [UNESP]; de Almeida, Fernanda Losi Alves; Nunes, Helga Caputo [UNESP]; Rinaldi, Jaqueline Carvalho; Felisbino, Sérgio Luis [UNESP] (Wiley, 2017)
Benign prostatic hyperplasia (BPH) is the most common cause of lower urinary tract symptoms (LUTS) in older men. In this regard, recent studies have attempted to define the relationships between prostatic fibrosis, LUTS, and increased expression of transforming growth factor β1 (TGF β1) in BHP. Therapeutic approaches for BPH such as 5-α-reductase inhibitors and alpha-adrenergic blocking agents increase TGF β1 expression in the prostatic tissue. Here, we investigated the effects of the 5-α-reductase inhibitor—finasteride—on rat ventral prostate tissue, especially with regard to the tissue distribution and gene expression of fibrillar collagens. Adult Wistar rats (n = 15) were treated with finasteride (25 mg/kg/day) by subcutaneous injection for 7 and 30 days. Age-matched, vehicle-treated (n = 15) adult Wistar rats were used as control. Finasteride treatment reduced prostate size and increased the area of types I and III collagen fibers in the prostatic stroma. As expected, TGF β1 mRNA expression was upregulated by finasteride treatment. However, COL1A1 and COL3A1 mRNA expressions decreased after both 7 and 30 days of finasteride treatment, suggesting that finasteride treatment promotes prostate parenchyma and stroma changes, which lead to the observed types I and III collagen remodeling without de novo collagen synthesis. The upregulation of TGF β1 mRNA and protein associated with the 5-α-reductase inhibitor is more closely related to epithelial and stromal cell death pathways than to prostatic fibrosis.
Keywords: collagen; fibrosis; finasteride; prostate; second harmonic; TGF β1